Computer-Assisted Surgery for Segmental Mandibular Reconstruction with the Osteoseptocutaneous Fibula Flap: Can We Instigate Ideological and Technological Reforms?. Issue 3 (March 2016) - Deek, Nidal Farhan A. L.; Wei, Fu-Chan
Abstract : Summary: Virtual surgical planning and computer-aided design and computer-aided modeling are promising technologies with a growing trend in contemporary head and neck reconstruction. Segmental mandibular reconstruction with the osteoseptocutaneous fibula flap is one of the fields in which these technologies are increasingly used. Perceived benefits are increased surgical precision, improved operative efficiency, and overall good outcomes. Nevertheless, these programs do not cover the reconstruction picture of interest thoroughly, at least in the mind of the experienced surgeon. Based on extensive experience in segmental mandibular reconstruction and comprehensive literature review, the authors attempted to identify missing dots in computer-aided mandibular reconstruction; when possible, a problem-solution approach was taken. Of these dots, pedicle reach to the recipient vessels, multiple target soft-tissue reconstruction, anatomical variations and cross-section topography of the osteoseptocutaneous fibula flap, and intraoperative modification of the surgical plan were understated or not considered in the phases of virtual surgical planning and execution. Moreover, with the relatively small experience reported in computer-aided segmental mandibular reconstruction compared with the well-appreciated challenges, further discussion of what could be a realistic and safe indication was deemed necessary. Following in the footsteps of the iPhone developer of creating software satisfying to customers (i.e., surgeons) first and armed with the evidence from the literature and accumulation of experience, this Special Topic article aims to provoke a discussion among experts in this field to instigate ideological and technological reforms in computer-aided mandibular reconstruction.